2018
DOI: 10.1080/10942912.2018.1425701
|View full text |Cite
|
Sign up to set email alerts
|

Composition and crystallization behavior of solvent-fractionated palm stearin

Abstract: Palm stearin (PS) is an extensively used trans-free hardstock. Depending on process parameters, fractions with unique compositions, hardness, and solid fat content can be tailored toward specific applications. In this work, the composition and crystallization of PS fractionated with acetone at 30°C, 35°C, or 40°C into various liquid (LF) and solid (SF) fractions were investigated. After fractionation, iodine value (IV) of PS changed from 37 to values ranging from 24 to 51. The IV of the LF increased with a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
5
30
0
Order By: Relevance
“…The modifications of the fatty acids observed in the BKF fractions were due to the dilution and solubilization of the fatty acids in the solvent fractionation. Our findings are in line with the findings of Zaliha, Chong, Cheow, Norizzah, and Kellens (2004), Marikkar, Saraf, and Dzulkifly (2013), Ahmad, Nadeem, Ayaz, and Jaspal (2015), and Podchong, Tan, Sonwai, and Rousseau (2018), who also reported the modifications in fatty acids after fractionation fats from different sources such as palm stearin, palm oil, milk fat, and coconut oil. After single or multi‐stages fractionation, the fatty acids in the BKF stearin (solid) and olein (liquid) fraction changes were found to be similar to those of fats.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The modifications of the fatty acids observed in the BKF fractions were due to the dilution and solubilization of the fatty acids in the solvent fractionation. Our findings are in line with the findings of Zaliha, Chong, Cheow, Norizzah, and Kellens (2004), Marikkar, Saraf, and Dzulkifly (2013), Ahmad, Nadeem, Ayaz, and Jaspal (2015), and Podchong, Tan, Sonwai, and Rousseau (2018), who also reported the modifications in fatty acids after fractionation fats from different sources such as palm stearin, palm oil, milk fat, and coconut oil. After single or multi‐stages fractionation, the fatty acids in the BKF stearin (solid) and olein (liquid) fraction changes were found to be similar to those of fats.…”
Section: Resultssupporting
confidence: 92%
“…The unsaturated fatty acids (mainly linoleic acid) were presumably the key factors for causing SMP variations in the samples. Similar decreasing and increasing trends for SMP were observed in solvent fractionated mango kernel fat and palm stearin fractions by Jin, Zheng, et al (2017) and Podchong et al (2018).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, it is a cheap, simple operation in which flavors are usually preserved. Dry fractionation obtains fractions with different physical properties than the original fat without producing trans fatty acids (Podchonga et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They found that as fractionation temperature was lowered, yield of fat crystals increased. Podchong et al (2018) investigated the fractionation of palm stearin using acetone. Their results supported that fat crystal yield obtained at 30 C was higher than at 35 and 40 C. Similarly, Kar et al (2015) reported that the crystal yields of coconut oil from isopropanol fractionation varied with the crystallization temperature, as 43 to 71% of fat crystals could be obtained when crystallized at temperature between 15 and 10 C, respectively.…”
Section: Yield and IVmentioning
confidence: 99%